Analisis Penggunaan Model Pembelajaran Project Based Learning Dalam Peningkatan Keaktifan Siswa - Putri Dewi Anggraini; Siti Sri Wulandari (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
This research has the aim to describe and describe the use of project based learning methods in terms of increasing student activity. The study was classified as a qualitative descriptive study. The subjects used in this study were students of class X OTKP at 2 Blitar Public Vocational School on Public Relations and Protocol. Data collection techniques used were observation and interviews. While data analysis techniques are used through several stages including data collection, data presentation and drawing conclusions. In the learning process students tend to be bored and less interested in the learning process that takes place because the method used is merely lecture and monotonous. Therefore this research was conducted so that students are more active in the learning process. The activeness of students in the learning process also has an important role in learning outcomes. The project based learning learning model is a scientific approach and consists of several stages, including observing, asking questions, gathering information, reasoning, and communicating. Through these various stages students can increase their role in the learning process.